2019
DOI: 10.1016/j.ajog.2018.11.528
|View full text |Cite
|
Sign up to set email alerts
|

506: A population-based definition for severe proteinuria and its association with adverse outcomes in preeclampsia

Abstract: sought to examine if race is associated with postpartum readmission due to hypertension in women with pregnancy-associated hypertension. STUDY DESIGN: This was a multi-institutional retrospective cohort study of all women with pregnancy-associated hypertension diagnosed prior to initial discharge from January 2009 to December 2016. Pregnancy-associated hypertension such as gestational hypertension and preeclampsia (with or without severe features) was diagnosed based on American College of Obstetricians and Gy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In the diagnosis of preeclampsia, hypertension was defined as the first occurrence of a systolic blood pressure ≥ 140 mmHg and a diastolic blood pressure ≥ 90 mmHg after the 20th week of pregnancy, measured at least twice at 4-h intervals in the left lateral decubitus position. A pregnant woman with no kidney disease was determined to have < 0.3 g in a 24-h urine sample for protein measurement in the third trimester [4]. All patients diagnosed with preeclampsia were followed up for 12 weeks after birth.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the diagnosis of preeclampsia, hypertension was defined as the first occurrence of a systolic blood pressure ≥ 140 mmHg and a diastolic blood pressure ≥ 90 mmHg after the 20th week of pregnancy, measured at least twice at 4-h intervals in the left lateral decubitus position. A pregnant woman with no kidney disease was determined to have < 0.3 g in a 24-h urine sample for protein measurement in the third trimester [4]. All patients diagnosed with preeclampsia were followed up for 12 weeks after birth.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the accurate determination of the severity of preeclampsia is important for identifying pregnant women at greater risk of complications. Recent publications have shown that severe proteinuria is valuable in the prediction of poor obstetric outcomes in women with preeclampsia [3,4]. In the past, the amount of proteinuria was important to assess the severity of preeclampsia [5].…”
mentioning
confidence: 99%
“…Bharathi et al ( 2019) [43] in their study of 209 antenatal women observed that out of the 157 preeclamptic women, complication rate among women with proteinuria >300 mg/day, >1000 mg/day, and >2000 mg/day were as follows: abruptio placenta: 33.3% vs. 66.7% vs. 0 (p<0.001); HELLP syndrome: 0 vs. 33.3% vs. 66.7% (p<0.001); and eclampsia: 11.7% vs. 77.8% vs. 11.7% respectively (p<0.001), which indicated a very strong significance. Speranza et al ( 2019) [44] in their retrospective study stated that renal complications were significantly more common among cases of preeclampsia with severe proteinuria. Martins-Costa et al ( 2011) [45] stated that hypertensive pregnant women with a PCR ≥0.3 mg/mg had worse maternal and perinatal outcomes than those with PCR <0.3 mg/mg.…”
Section: Kim Et Al (2017)mentioning
confidence: 98%